2020
DOI: 10.1111/jsr.12996
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic relationship between daily caffeine intake and sleep duration in middle‐aged and older adults

Abstract: Insufficient sleep duration has become a growing health problem. According to the Centers for Disease Control and Prevention, more than one-third of American adults do not get enough sleep on a regular basis (Liu et al., 2014). Research has shown that there is an inverse relationship between caffeine consumption and sleep duration (e.g., Bonnar & Gradisar, 2015; Hicks, Hicks, Reyes, & Cheers, 1983; Hollingworth, 1912; etc.). Caffeine is also believed to prolong sleep latency, reduce sleep efficiency and worsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Although caffeine consumption has been linked to sleep disturbances, shorter sleep duration, and poorer perceived sleep quality in healthy adults [ 34 ], we did not observe this association in a representative sample of community-dwelling older males and females in The Netherlands. Our results are consistent with a previous observational study in middle-aged and older adults that found no association between self-reported caffeine consumption and sleep duration measured using actigraphy [ 38 ]. Most other studies evaluated caffeine intake from coffee consumption only [ 36 , 37 , 39 ], which may have led to a misclassification of subjects and an underestimation of associations.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although caffeine consumption has been linked to sleep disturbances, shorter sleep duration, and poorer perceived sleep quality in healthy adults [ 34 ], we did not observe this association in a representative sample of community-dwelling older males and females in The Netherlands. Our results are consistent with a previous observational study in middle-aged and older adults that found no association between self-reported caffeine consumption and sleep duration measured using actigraphy [ 38 ]. Most other studies evaluated caffeine intake from coffee consumption only [ 36 , 37 , 39 ], which may have led to a misclassification of subjects and an underestimation of associations.…”
Section: Discussionsupporting
confidence: 93%
“…Controlled laboratory experiments and observational studies in adults have indicated that caffeine consumption can prolong sleep latency (the time it takes to fall asleep after going to bed) and reduce sleep duration, efficiency (defined as the ratio of total sleep time to time spent in bed), and perceived sleep quality [ 34 , 35 ]. However, few studies have examined the relationship between caffeine consumption and sleep health in older adults [ 36 , 37 , 38 , 39 , 40 ], despite the high prevalence of sleep disturbances and disorders in this population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve this goal, clinicians can recommend evidence-based strategies to older adults for promoting adequate TIB and improving sleep quality. For example, listening to soft music at bedtime [38], reducing caffeine intake and being aware that older adults may be more sensitive to caffeine compared to younger adults [39,40], evening light exposure [41] and light therapy [42]. Future longitudinal studies are warranted to explore the causal relationship between physical activity, time in bed, and sleep duration.…”
Section: Resultsmentioning
confidence: 99%